The Effect of CO2 Dilution on the Laminar Burning Velocity of Premixed Methane/Air Flames. (August 2015) - Chan, Y.L.; Zhu, M.M.; Zhang, Z.Z.; Liu, P.F.; Zhang, D.K.
Abstract: The effect of CO2 dilution on the laminar flame speed of methane/air mixture was studied by means of experimentation and kinetic modelling. Experiments were conducted using a flat-flame burner at atmospheric pressure and 298K over the methane/air equivalence ratio range of 0.8 to 1.4. Kinetic modelling was performed using Chemkin Pro, with the skeletal version of Le Cong et al 's kinetic mechanisms. It was found that the laminar flame speeds measured using the flat flame method were accurate, supported and validated by the literature data. The laminar flame speed of CH4 /air decreased with increasing CO2 dilution. The increase in CO2 concentration reduced the reactants' concentrations, decreasing the net reaction rate (and thus the flame speed). In addition, CO2 also acts as a heat sink, causing a drop in the reaction temperature and thus lowering the ability to overcome the activation energy for reactions to occur. This study contributes to the understandings of the effect of inert gas on the flammability characteristics of methane.